A Survey on Chemistry Students’ Ability to Summarize Articles in English - Kalila Yasmin; Taufik Aldi Dzamir Rabbani; Wahyunengsih Wahyunengsih (STKIP Taman Siswa Bima, 2025)
English is widely used as the main language of scientific communication, making the ability to read and summarize English scientific articles essential for chemistry students. However, many students experience difficulties in identifying main ideas, paraphrasing information, and understanding scientific vocabulary. This study aims to investigate chemistry students’ ability to summarize English scientific articles, including the strategies used, the role of vocabulary mastery, and the challenges encountered. An explanatory sequential mixed-methods design was employed. Quantitative data were collected through vocabulary and summarizing tests, while qualitative data were obtained from classroom observations and interviews. The participants were undergraduate chemistry students with varying levels of English proficiency. The results indicate that students showed improvement in vocabulary use and summary writing after participating in multimedia-based English for Science instruction. In addition, bilingual scaffolding helped students better understand scientific texts and increased their confidence in using English. Overall, this study suggests that context-based English for Science instruction can support students’ academic reading and summarizing skills.